Design and Development of Website and Android-Based Aceh Biodiversity Applications - Muhammad Subianto; Essy Harnelly; Alim Misbullah; Razief Perucha Fauzie Afidh; Fikrul Akhyar; Muhammad Irfan; Wira Dharma; Nazaruddin; Zulfan (Postgraduate, University of Mataram, 2025)
Aceh is an exceptional region in Indonesia characterized by significant biodiversity and abundant natural wealth. Despite these numerous benefits, there is limited information regarding the potential of biodiversity in this region. Therefore, this research aimed to design and develop Website and Android-based applications to facilitate access to information regarding biodiversity in Aceh. In the development process, the Waterfall method was used, and the applications consisted of two main components, namely the back-end and the front-end. The users were divided into three categories, including contributors, verificators, and admins. After the development was complete, functionality testing was conducted using the black box method, and usability was examined using the Post-Study System Usability Questionnaire (PSSUQ). The results of functionality testing showed that both applications operate efficiently, thereby providing users with a satisfying experience when accessing information about Aceh biodiversity. The usability score was approximately 7 for Website-based and 6 for Android-based applications, showing a high level of usability.